Learning process in faith: from the possibilities of learning to the results in experience - Wischral Rodrigues, Marilze (Vox Scripturae - Revista Teológica Internacional, 2024)
The dialogue between theology and pedagogy builds the basis for the development of the learning process from the perspective of faith. It is not faith that grows, but rather people who mature in attitudes that correspond to the hope they confess, concrete attitudes in their daily lives. Considering the cognitive, affective and attitudinal dimensions of the human being, this research has as its main objective to describe learning that is integral, significant and continuous, from the perspective of faith. Therefore, in addition to bibliographical research, an exegetical analysis of biblical texts that support each of these learnings was carried out. It is important to consider the existential context of students, establishing the link between faith and life, promoting integral, significant learning and continuous formation in the faith, that is, in each phase of life. The task of continuous formation in the faith is the responsibility of all people who participate in life in the Christian community, evidencing the general priesthood of all people who believe in an effective and efficient way. The Church of Jesus Christ is concerned with the catechumenate, with ongoing discipleship, with the formation in the faith of children, adolescents and young people, as well as adults and the elderly, planning and implementing in a conscious and responsible way the integral and significant learning in the process of formation in the faith throughout life.